A MULTIDISCIPLINARY EVALUATION OF HEALTHCARE ADMINISTRATION, NURSING, AND HEALTH INFORMATION TECHNOLOGY PRACTICES IN SAUDI ARABIAN HOSPITALS - Mohammad Obaid Abdullah Alomari 1, Ibrahim Zaher Matouq Althagafi 2, Omer Abdullah Mohammed Alshaikhi 3, Ahmad Dhaifallah Mohammed Alzahrani 4, Abdolrahman Ategallah Modhi Alsolami 5,; Sultan Mohammed Ahmed Albinessa 6, Abdullah Mohammed Al hutaylah 7, ‏Mohmmad Raziq Muriziq Alyazidi 8 (Chelonian Research Foundation, 2022)
This extensive mixed methods study evaluated the practices and perspectives of healthcare administrators, nurses, and health information technology (HIT) professionals regarding hospital management, nursing services, and HIT systems in Saudi Arabia. Quantitative survey data was collected from 500 administrators, 800 nurses, and 600 HIT staff across 20 hospitals. Additionally, 60 qualitative interviews were conducted with 20 participants from each group. Surveys revealed widespread nurse understaffing, poor adherence to evidence-based protocols, and lack of integrated HIT systems. Interviews highlighted challenges with fragmented leadership, communication breakdowns, outdated technologies, and lack of training. Key recommendations include improving nurse-patient ratios, implementing care standardization, optimizing HIT infrastructure, strengthening team collaboration, and enhancing competency-based education across administrative, nursing, and HIT domains. This robust multidisciplinary evaluation provides an in-depth understanding of gaps in hospital practices in Saudi Arabia while extensively triangulating insights from diverse stakeholders. Findings can significantly inform healthcare leaders on interventions to advance hospital performance, quality, and patient outcomes through integrating administration, nursing, and HIT perspectives.